1983
DOI: 10.1172/jci110786
|View full text |Cite
|
Sign up to set email alerts
|

2-Methylthioadenosine[beta-32P]diphosphate. An agonist and radioligand for the receptor that inhibits the accumulation of cyclic AMP in intact blood platelets.

Abstract: A B S T R A C T 2-Methylthio-ADP and its radioactive analogue [,_-32P]2-methylthio-ADP were synthesized and used to investigate platelet receptors for ADP. 2-Methylthio-ADP induced platelet aggregation and shape change, and inhibited cyclic AMP accumulation in platelets exposed to prostaglandin El. Compared with ADP, 2-methylthio-ADP was 3-5 times as active as an aggregating agent and 150-200 times as active as an inhibitor of cyclic AMP accumulation. Binding of [#-32P]2-methylthio-ADP to platelets was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 10 publications
5
58
1
Order By: Relevance
“…As expected, DTT strongly inhibited the binding as did the chemical pCMBS which is a well-known inhibitor of ADP-induced platelet aggregation [9,[26][27][28]43]. Since DTT was present in our previous membrane preparations to preserve them from oxidation, it is not surprising that we could not observe any difference between clopidogrel treated and control rats.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…As expected, DTT strongly inhibited the binding as did the chemical pCMBS which is a well-known inhibitor of ADP-induced platelet aggregation [9,[26][27][28]43]. Since DTT was present in our previous membrane preparations to preserve them from oxidation, it is not surprising that we could not observe any difference between clopidogrel treated and control rats.…”
Section: Discussionsupporting
confidence: 64%
“…One important point is to be able to quantify the number of receptors expressed on platelets in order to assess the inter-individual variability in the general population, to characterize patients with inherited deficiencies, and to monitor and study patients treated with P2Y 12 targeting drugs [4]. Various radioligands have been used to characterize and quantify the platelet P2Y receptors such as, [ 14 C]ADP [5,6], [ 3 H]ADP [6,7], [ 3 H]2-methylthio-ADP [8], [β- 32 P]2-methylthio-ADP [9,10], and [β- 33 P]2-methylthio-ADP [11], but they all share several weaknesses: (a) They are metabolically unstable and may be cleaved by a number of enzymes such as alkaline phosphatase and ectonucleotidases; (b) being agonists, they may complicate the quantification when intact, living cells are used and receptors are internalized upon activation; (c) they do not discriminate between P2Y 1 and P2Y 12 receptors. In the last decade, the only one possibility to selectively quantify P2Y 12 receptors was to use the non-selective radiolabeled ligand 2-methylthio-ADP in the presence of a P2Y 1 antagonist such as N 6 -methyl-2′-deoxyadenosine-3′,5′-bisphosphate (MRS2179) [12] or 2-iodo-N 6 -methyl-(N)-methanocarba-2′-deoxyadenosine-3′,5′-bisphosphate (MRS2500) [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the 1980s, by the use of 2-azido-ADP that could be photoactivated [94] and also a strong aggregating ADP analogue, 2-methylthioadenosine labelled with 32 P (2-MeS-ADP), Macfarlane and colleagues [95] obtained values ranging from 400 to 1,200 sites per platelet for the receptor that inhibits adenylyl cyclase (P2Y 12 ). More recently, using the latter analogue, Gachet et al [96] reported 600±125 specific binding sites per platelet, and Nurden and co-workers [97] found 826±126 per platelet.…”
Section: Binding Sites For Adp On Plateletsmentioning
confidence: 99%
“…In 1983, Macfarlane et al [95] had demonstrated that the thiol complexing agent p-mercuribenzene sulfonate blocks inhibition by ADP of adenylyl cyclase and blocks the binding of 2-azido-ADP and 2-MeS-ADP, but does not affect the ability of ADP to induce aggregation and the shape change. In 1993, Cristalli and Mills [98] showed that a 43-kDa protein on platelets incorporated 2-(p-azidophenyl)-ethylthio-ADP (AzPET-ADP), a photoaffinity analogue of ADP that competitively inhibits the binding of 2-MeS-ADP.…”
Section: Binding Sites For Adp On Plateletsmentioning
confidence: 99%
See 1 more Smart Citation